Verbu pagātnes formas 16. gs.–17. gs. sākuma latviešu rakstu valodā un pagātnes celmu tālākais liktenis - Vanags, Pēteris (Baltistica, 1996)
THE FORMS OF THE IMPERFECT IN THE 16th–17th C. WRITTEN LATVIAN AND THE FURTHER FATE OF THE IMPERFECT STEMSIn this paper, the author deals with the history of the forms of the imperfect in written Latvian. At first the author analyses imperfect forms from all the written sources of Latvian in the 16th and early 17th century. It is obvious that different sets of endings of historical ā- and ē- stems existed at this time yet, but the process of neutralising had already started. It seems that in the area of written language this process began with the excluding of original palatalization from the 1st person singular forms of certain type of historically ē-stem verbs. The second step of development was the spreading of ā-stem endings to the 1st and 2nd person plural, and the last one – the neutralization of different endings of the 3rd person. Most dialects instilled the ending -a for all the verbs, but in the written language, probably on the basis on some local dialect, the ending -e was used for most unsuffixed verbs until the middle of the 19th century.
Keywords: latvių kalba; veiksmažodis; būtasis laikas